NILAI KERUKUNAN ETNIS JAWA TERHADAP MOTIVASI BERPERILAKU MASYARAKAT JAWA: PSIKOLOGI BUDAYA - Fadilah Hasyim, Farah; Hasneni; Cinnong, Shabrina; Amar, Nurfadhila Naifah; Pirri, Juliette Tamarischa (JURNAL ILMU BUDAYA, 2023)
The aim of this study is  to examine the value of Javanese community harmony which influences the behavior of Javanese people, as well as how globalization affects the values of Javanese ethnicity. This study uses a literature review (LR), namely the synthesis of a systematic, clear, identifiable study of literature, analysis using the explicit search method, the critical review process in selecting research.  The results showed that Javanese culture has a harmony value which aims to maintain society in a harmonious state and avoid conflict. Also, there is an influence of the value of Javanese cultural harmony on behavior motivation, affiliation motivation, pro-social motivation, emotion expression motivation, and entrepreneurial motivation in Javanese cultural communities.